Effect of Cash Flow on Liquidity Levels in PT. by Pekebunan Nusantara VI - johandri iqbal; Heriyani; Virnanda Nurlina (Universitas Islam Lamongan, 2023)
This study aims to test the influence of cash flows on the level of liquidity present in PT. Farming of Nusantara VI. This study uses quantitative methods with causal relationships. (sebab-akibat). The research consists of four variables, namely, operating activity, investment activity and financing activity as free variables with liquidity as bound variables. The population in this study is a financial report on PT. The Nusantara VI plantation begins in 2018-2021 and uses 16 samples of triwulan reports each year. Data analysis techniques in this study use classical assumption testing, double linear regression analysis, t test, F test and determination coefficient. Data processing in this study uses SPSS software. The results of the research showed that, in part, the cash flow of operational activity, investment activity cash flow and financing cash flow have a significant impact on liquidity. Simultaneously the cash flow of operational activity, the cash flows of investment activity, and the funding cash flow also have a significant influence on liquidity in PT. Farming of Nusantara VI